ECCO2R in 12 COVID-19 ARDS Patients With Extremely Low Compliance and Refractory Hypercapnia - Ding, Xin; Chen, Huan; Zhao, Hua; Zhang, Hongmin; He, Huaiwu; Cheng, Wei; Wang, Chunyao; Jiang, Wei; Ma, Jie; Qin, Yan; Liu, Zhengyin; Wang, Jinglan; et al. (Frontiers in Medicine, 2021)
Purpose: A phenotype of COVID-19 ARDS patients with extremely low compliance and refractory hypercapnia was found in our ICU. In the context of limited number of ECMO machines, feasibility of a low-flow extracorporeal carbon dioxide removal (ECCO2R) based on the renal replacement therapy (RRT) platform in these patients was assessed. Methods: Single-center, prospective study. Refractory hypercapnia patients with COVID-19-associated ARDS were included and divided into the adjusted group and unadjusted group according to the level of PaCO2 after the application of the ECCO2R system. Ventilation parameters [tidal volume (VT), respiratory rate, and PEEP], platform pressure (Pplat) and driving pressure (DP), respiratory system compliance, arterial blood gases, and ECCO2R system characteristics were collected. Results: Twelve patients with refractory hypercapnia were enrolled, and the PaCO2 was 64.5 [56-88.75] mmHg. In the adjusted group, VT was significantly reduced from 5.90 ± 0.16 to 5.08 ± 0.43 ml/kg PBW; DP and Pplat were also significantly reduced from 23.5 ± 2.72 mmHg and 29.88 ± 3.04 mmHg to 18.5 ± 2.62 mmHg and 24.75 ± 3.41 mmHg, respectively. In the unadjusted group, PaCO2 decreased from 94 [86.25, 100.3] mmHg to 80 [67.50, 85.25] mmHg but with no significant difference, and the DP and Pplat were not decreased after weighing the pros and cons. Conclusions: A low-flow ECCO2R system based on the RRT platform enabled CO2 removal and could also decrease the DP and Pplat significantly, which provided a new way to treat these COVID-19 ARDS patients with refractory hypercapnia and extremely low compliance. Clinical Trial Registration:https://www.clinicaltrials.gov/, identifier NCT04340414.